The Local Linear M-Estimation with Missing Response Data. (29th June 2014) - Luo, Shuanghua; Zhang, Cheng-Yi; Xu, Fengmin
Abstract : This paper studies the nonparametric regressive function with missing response data. Three local linear M -estimators with the robustness of local linear regression smoothers are presented such that they have the same asymptotic normality and consistency. Then finite-sample performance is examined via simulation studies. Simulations demonstrate that the complete-case data M -estimator is not superior to the other two local linear M -estimators.